Tensions in teacher preparation accountability, assessment, and accreditation - Erickson, Lynnette B.; Wentworth, Nancy (Advances in research on teaching ;, 2010)
Current accreditation practices require that teacher education institutions in the United States not only create programs that enact research-based best practices but that they also document their existence and efficacy in preparing teachers. 'Tensions in Teacher Preparation: Accountability, Assessment, and Accreditatio' addresses the challenges of meeting national accreditation requirements, including designing assessment instruments and making data-driven decisions. The process of establishing and implementing accountability creates tensions in faculty and institutions. Faculty must give up valued content and instructional styles in order to align course objectives and assessment instruments across the program. Institutions with multiple licensure programs must make adjustments in order to share data collection instruments and processes that will support data-driven decisions. The paradigm shifts required by the emphasis on accountability can be both frustrating and productive. This book explores and shares tensions created as teacher education programs experience changes because of accountability requirements related to the accreditation process.